Endangered Przewalski’s Horse, Equus przewalskii, Cloned from Historically Cryopreserved Cells - Ben J. Novak; Oliver A. Ryder; Marlys L. Houck; Kelcey Walker; Lexie Russell; Blake Russell; Shawn Walker; Sanaz Sadeghieh Arenivas; Lauren Aston; Gregg Veneklasen; Jamie A. Ivy; Klaus-Peter Koepfli; et al. (Animals)
Cloning from historically cryopreserved cells offers a potential means to restore lost genetic variation or increase the representation of particular lineages within bottlenecked species, provided such biobanked materials are archived for such genetic rescue applications. One species for which cloning can provide genetic management benefits is Przewalski’s horse, Equus przewalskii. All ~1800 living Przewalski’s horses, distributed across ex situ breeding facilities and in situ reintroduction sites, are descended from one or more of the five founder lineages established by the 12 horses captured from the wild between 1898 and 1947. Since the 1970s, the San Diego Zoo Wildlife Alliance Biodiversity Bank’s Frozen Zoo® (Escondido, CA, USA) has biobanked cells or tissues of 575 individuals spanning many generations. A pedigree analysis of a subset of deceased individuals represented in the San Diego Zoo Wildlife Alliance Biodiversity Bank’s Frozen Zoo® revealed an underrepresented male that lived from 1975 to 1998, Studbook Number 615 (also known as Kuporovitch), who would be of high value for breeding if cloned. Here, we report that two healthy clones were produced from this cell line using cross-species somatic cell nuclear transfer from 2020 to 2023. Their identification as clones was verified by a standard horse-pedigree genotyping panel, and, for one clone, a whole genome sequencing comparison to the original donor was performed. This is the first time that multiple healthy clones surviving the perinatal period have been produced for an endangered species.